2003
DOI: 10.1007/s10350-004-6729-4
|View full text |Cite
|
Sign up to set email alerts
|

Modified Bascom's Asymmetric Midgluteal Cleft Closure Technique for Recurrent Pilonidal Disease

Abstract: The suggested modified Bascom technique is an attractive, safe, easily performed operation with minimal morbidity and can be reliably used as a second-line surgical option for recurrent pilonidal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 17 publications
2
25
0
3
Order By: Relevance
“…Theodoropoulos et al . , who excised the sinus tissue in patients with recurrent disease, also found a similar wound complication rate to the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Theodoropoulos et al . , who excised the sinus tissue in patients with recurrent disease, also found a similar wound complication rate to the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Studies have shown it to be excellent in refractory cases of pilonidal disease [5,12]. There is a growing community of adult general and colorectal surgeons who believe that the cleft lift procedure is one of the preferred techniques in treating moderate and severe chronic and refractory pilonidal disease [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Techniques such as the Bascom flap procedure and the elliptical rotation flap have been developed, using wound closure away from the midline without tension. 13,14,17,27 It is shown that these types of approaches result in faster healing time and a reduced recurrence rate compared with open healing. 16 The background is an assumption that pilonidal disease primarily is a superficial skin disease that secondarily involves the deeper SC tissue.…”
Section: Discussionmentioning
confidence: 99%